The Effect of Smart (Self Monitoring Approach to Read And Think) Strategy In Students’ Reading Comprehension at SMAN 4 Kota Bengkulu - Candra Fangesti (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The objective of the research was to find out the effect students reading comprehension after being trough SMART (Self Monitoring Approach to Read and Think) strategy in reading comprehension. The design of this research was experimental research. The instrument of the research was reading comprehension test. The result showed SMART (Self Monitoring Approach to Read and Think) was effective to be used to students’ ability in reading comprehension because there was a significant difference between the progresses in writing of the students who were studying through SMART strategy and those are not. By SMART strategy was effective to improve students’ comprehension in the aspect of finding main idea and identifying specific information. It is suggested for English teacher: it is expected for the teacher to use this strategy to make students enjoy their time to read the text in the classroom. Afterthat, in order to increase the students scores reading comprehension, the teachers are expected use the variation strategy and choose the best strategy, like SMART or another strategy that can help improvement of students ability and the students do not feel bored to learn. Key words: Reading Comprehension, SMART Strategy, Desscriptive Text